Smart classroom adoption in higher education: a thematic review - Mohd Zairul; Ismail, Ismi Arif; Mohamad Jamil, Mohd Azli; Azlan, Aznida; Ismail, Ida Suriana; Ab Jalil, Habibah; Mohamad Sharef, Nurfadhlina (Human Resource Management Academic Research Society, 2022)
Smart classroom has become a much popular terms in 21st century education recently. The concept of intelligence has created interest among the key players in higher education especially in the era IR 4.0. However, prior research revealed that there is no review paper that talks about the patterns in smart classroom adoption in the higher learning. Hence, this article will conduct a thematic review on the selected publications to explore the direction of this initiative until recent years. The aim of this thematic review is to synthesize literature from 2017 to 2021 on the smart classroom strategies in the higher education using thematic review (TR). A keyword search, followed by a filter using inclusion criteria from SCOPUS, WoS and Science Direct databases, identified 116 peer-reviewed journal articles. However, after the inclusion and exclusion process, only 79 articles were used as the final articles to be reviewed. A thematic review of the 79 articles identified four themes characterizing space, technology, pedagogy and feedback. The results benefit the future study on smart classroom research and what can be the future directions of the study. However, this study only limited to database from SCOPUS, WoS and Science direct for the purpose of thematic review.